Body contouring surgery in a massive weight loss patient: An overview - Prabhat Shrivastava; Aggarwal Aditya; Khazanchi Rakesh Kumar (Indian Journal of Plastic Surgery)
The number of patients with history of extreme overweight and massive weight loss (MWL) has risen significantly. Majority of patients are left with loose, ptotic skin envelopes, and oddly shaped protuberances, subsequent to weight loss. Redundant skin and fat can be seen anywhere on the body following MWL. This group of population presents many unique problems and challenges. Body contouring surgery after MWL is a new and exciting field in plastic surgery that is still evolving. Conventional approaches do not adequately cater to the needs of these patients. Complete history, detailed physical examination, clinical photographs and lab investigations help to plan the most appropriate procedure for the individual patient. Proper counseling and comprehensive informed consent for each procedure are mandatory. The meticulous and precise markings based on the procedure selected are the cornerstones to achieve the successful outcome. Lower body contouring should be performed first followed six months later by breast, lateral chest and arm procedures. Thighplasty is usually undertaken at the end. Body contouring operations are staged at few months′ intervals and often result in long scars. Staging is important as each procedure can have positive impact on adjacent areas of the body. Secondary procedures are often required. However, proper planning should lead to fewer complications and improved aesthetic outcome and patient satisfaction.